2017
DOI: 10.1007/s00167-017-4438-5
|View full text |Cite|
|
Sign up to set email alerts
|

Relaxation of the MCL after an Open-Wedge High Tibial Osteotomy results in decreasing contact pressures of the knee over time

Abstract: PurposeThe objective of this study was to investigate the effect of a medial open-wedge osteotomy (OWO) and the release of the superficial medial collateral ligament (MCL) on the tibiofemoral cartilage pressure, the MCL tension and the valgus laxity of the knee.MethodsSeven fresh-frozen, human cadaveric knees were used. Medial and lateral mean contact pressure (CP), peak contact pressure (peakCP), and contact area (CA) were measured using a pressure-sensitive film (I-Scan; Tekscan, Boston, MA). The MCL tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
(53 reference statements)
1
26
1
Order By: Relevance
“…Studies seem to confirm these presumptions. Van Egmond et al 10 . reported in their cadaveric study that after releasing the sMCL, the mean contact pressure, peak contact pressure, and contact area decreased in the medial compartment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies seem to confirm these presumptions. Van Egmond et al 10 . reported in their cadaveric study that after releasing the sMCL, the mean contact pressure, peak contact pressure, and contact area decreased in the medial compartment.…”
Section: Discussionmentioning
confidence: 96%
“…Although the effectiveness of the HTO seems to be clear, there are still some debates on the technical details of this procedure to obtain better outcomes 9, 10, 11. It is clear that during HTO, release of the sMCL should be performed because omitting it might not allow for proper osteotomy gap opening and may result in overstress on the medial compartment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1 , various studies showed that performing an OWHTO without any release of the sMCL results in an increase of the sMCL strain, an increase in the contact area and pressures on the medial tibiofemoral compartment, and a decrease in these parameters on the lateral compartment [ 18 , 27 , 28 ]. This condition, which is in contrast with the objective of performing OWHTO, can even be deteriorated by increasing the size of the opened wedge.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment of meniscal injuries has undergone a number of developments over the past two decades, moving from open arthroscopic surgery; from total to partial meniscectomy and adding novel treatments; such as repair using a variety of devices, materials, transplants, collagen implants or xenografts ( Kim et al, 2013 ; Jiang et al, 2012 ; Grogan et al, 2017 ; Baek et al, 2017 ). If meniscectomy takes place or insisted upon, this procedure is mainly due to changes in load distribution across the articular cartilage as studies have shown that following total meniscectomy peak contact pressures increase by 253% and 165% following partial meniscectomy ( Lee et al, 2006 ; Baratz, Fu & Mengato, 1986 ; Beamer et al, 2017 ; Van Egmond et al, 2017 ). Following meniscectomy, there is also evidence of reduced muscle strength, altered gait patterns and clinical outcomes ( Hall et al, 2013 ; Hall et al, 2014 ; McLeod et al, 2012 ; Sturnieks et al, 2008a ; Sturnieks, Besier & Lloyd, 2011 ; Sturnieks et al, 2008b ; Salata, Gibbs & Sekiya, 2010 ; Scholes et al, 2017 ).…”
Section: Meniscusmentioning
confidence: 99%